Identifikasi dan Penghitungan Koloni Bakteri menggunakan Ektraksi Fitur - Satriyo Satriyo; Suheri Suheri; Pausta Yugianus (Vokasi, 2019)
Testing of bacterial contamination in food and beverage products is carried out by breeding bacteria in product samples. After the bacteria multiply in the sample, the number of colonies is calculated on the sample. The processing process requires time and accuracy of the laboratory. The purpose of this study is to build an application for identification and calculation of bacterial colonies using feature extraction methods. From the results of experiments on 11 sample samples of 81,82% bacterial colonies successfully identified.